Efektivitas Pemberian Makanan Tambahan Pemulihan (PMT-P) Terhadap Kenaikan Berat Badan Balita Stunting - Komalasari, Komalasari; Fara, Yetty Dwi; Utami, Iis Tri; Mayasari, Ade Tyas; Komalasari, Vitria; Al Tadom, Nurlaelah (Utan Kayu Publishing, 2021)
Indonesia still faced serious nutritional problems which are in line with the high number of stunting cases. The results of Basic Health Research show that the prevalence of stunting in Indonesia reached 30.8%Â in 2018 and fell to 27.7% in 2019. Compared to the results of the Indonesian Toddler Nutrition Status Survey (SSGBI), the incidence of stunting in Indonesia was successfully reduced to 3.1% in the last year. However, this data was still higher than the World Health Organization (WHO) limit on stunting, which is less than 20%. Lampung is the 36th city with the highest prevalence of stunting. The number of toddlers in the short and very short categories in 2018 almost reached 30%. Handling stunting in Lampung was divided into two priorities or stunting loci, namely the first and second priorities. The first priority was the area of South Lampung, East Lampung and Central Lampung, while the second priority was the Tanggamus area, one of which is Sinar Petir Village which is included in the working area of the Bulok Public Health Center. The results of a preliminary survey conducted by researchers in January 2020 at the Bulok Public Health Center, it was revealed that there were 32 cases of stunting in the period January to December 2019. The toddlers diagnosed with stunting will be given supplementary feeding that are high in calories and protein as well monitored through the Integrated Service Post of toddlers every month to determine their progress. This study used a quantitative research design with a retrospective cohort approach. The data were taken through the medical records of the Public Health Center and the MCH handbook of Toddler stunting. Weight gain will be displayed in the form of the average (mean) weight per month after the Toddler has received recovering supplementary feeding. The monitoring was carried out up to 3 months after the giving of recovering supplementary feeding.